FORMATION OF A HEALTHY LIFESTYLE - A WAY TO IMPROVE HEALTH - Karimboev Sh.D; Abdurashitova Sh.A; Muyassarova M.M; Nazarova N.B; Mamedova G.B (Scholar Express Journals, 2023)
The article is devoted to determining the attitude of senior students - courses of the medical institute to the problem of forming a healthy lifestyle in relation to themselves as a person, determining the degree of their participation in active recreation, sports and physical culture, combating psycho-emotional stress under the influence of various risk factors determined by them.
Keywords: students' health; medical universities; medical students; risk factors